Postoperative Depression: Insight, Screening, Diagnosis, and Treatment of Choice - Subiantoro, Risza; Margarita M Maramis; Nining Febriana; Lestari Basoeki; Sasanti Yuniar; I Gusti Ayu Indah Ardhani (Jurnal Psikiatri Surabaya, 2024)
Introduction: Postoperative depression is a condition of depressive effects in patients without symptoms of depressive mood that occurs a few weeks after surgery and persists for at least 2 weeks. It generally possesses the same symptoms as major depressive disorder. Review: Their difference is that surgery is the trigger of depression in postoperative depression cases. Postoperative depression is associated with increased patients’ morbidity and mortality, increased the risk of disease complications, reduced postoperative healing process, prolonged the duration of treatment, and reduced patients’ quality of life. Therefore, mental health conditions should always be assessed on patients after undergoing surgery. Postoperative depression therapy needs to consider the benefits of antidepressants and adequate pain management. Antidepressant considerations also need to consider interactions with other drugs. Psychotherapy and cognitive behavioral therapy are also useful in postoperative depression management. Conclusion: This review is aimed to give insight about postoperative depression, its importance, and how to treat it.